Criminalization of Fishermen in Kuala Langkat Village, Tanjung Pura District, Langkat Regency, North Sumatra - Dwi Kasih Meisania; Siregar, Abdul Rachman Maulana (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
This article examines the criminalization of traditional fishermen who are defending mangrove forests from conversion to palm oil plantations in Kuala Langkat Village, Tanjung Pura District, Langkat Regency. This conflict reflects the disparity in power relations between coastal communities and corporations supported by some state apparatus. The research uses a descriptive qualitative approach by gathering information from news articles and analyzing legal documents as well as environmental policies. The findings indicate that fishermen who maintain their fishing grounds are accused of damaging plantation facilities and illegally occupying land. This criminalization overlooks the fact that mangrove forests are a primary source of livelihood and ecological protection for the community. The article recommends an ecological justice approach and legal protection for traditional fishermen in coastal agrarian conflicts.